(untitled) (Research, Society and Development, 2022)
Introduction: Excessive gingival exposure or “gummy smile” presents an esthetic challenge that can be treated by different modalities, depending on the underlying etiologies. Objective: The objective of this study was to report the periodontal treatment of a case of gummy smile, discussing the associated etiological factors. Case report: Patient O.S.M.A., female, 23 years old, sought the Extension Project in Clinical and Surgical Periodontics (PROEPECC) demonstrating dissatisfaction with her smile, in which she had short clinical crowns and excessive gingival exposure. After clinical examinations, it was identified that it was a condition of type I B altered passive eruption and upper lip hypermobility. The proposed treatment was open field gingivectomy with osteotomy. Results: Since the immediate postoperative period, the patient already showed a significant improvement in her smile. The patient was reassessed at 6 months after surgery and a more harmonious smile was observed, as had been initially planned, with gingival tissues with regular contours and gingival zenith of central, lateral and canine incisors properly positioned. Conclusion: Excessive gingival exposure caused by altered passive eruption has an excellent prognosis when the case is well diagnosed and planned, observing the multifactorial etiology of gummy smile.